2018
DOI: 10.2196/humanfactors.8004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Usability and Usefulness of a Mobile App for Atrial Fibrillation Using Qualitative Methods: Exploratory Pilot Study

Abstract: BackgroundAtrial fibrillation (AFib) is the most common form of heart arrhythmia and a potent risk factor for stroke. Nonvitamin K antagonist oral anticoagulants (NOACs) are routinely prescribed to manage AFib stroke risk; however, nonadherence to treatment is a concern. Additional tools that support self-care and medication adherence may benefit patients with AFib.ObjectiveThe aim of this study was to evaluate the perceived usability and usefulness of a mobile app designed to support self-care and treatment a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…Most of the articles reviewed included populations inhabiting developed countries, apart from one that focused on a developing country (South Africa). Most of these qualitative studies focused on the United States [21,23-25,27,31,34,36,41,43,45,47,48,54] and the United Kingdom [30,32,35,42,53,61]. Other countries included were the Netherlands [22,33,44], Denmark [26,55,58], Sweden [38,40,49], Australia [28,29,46], Canada [50,56], South Africa [62], Singapore [59], China [63], Germany [37], Ireland [57], Belgium [60], Spain [39], and Switzerland [52].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the articles reviewed included populations inhabiting developed countries, apart from one that focused on a developing country (South Africa). Most of these qualitative studies focused on the United States [21,23-25,27,31,34,36,41,43,45,47,48,54] and the United Kingdom [30,32,35,42,53,61]. Other countries included were the Netherlands [22,33,44], Denmark [26,55,58], Sweden [38,40,49], Australia [28,29,46], Canada [50,56], South Africa [62], Singapore [59], China [63], Germany [37], Ireland [57], Belgium [60], Spain [39], and Switzerland [52].…”
Section: Resultsmentioning
confidence: 99%
“…Most of the apps under consideration were tailored to deal with chronic diseases: cancer [22,30,33,38,40,56,63]; HIV [23,24,31,45,48]; diabetes [28,50,55]; hypertension and cardiovascular diseases [43,54,57]; chronic kidney disease [27,42]; cystic fibrosis [21,51]; chronic pain [26,58]; juvenile arthritis [35,61]; brain and spinal cord anomalies [34]; multiple sclerosis [52]; chronic illnesses, in general [25,62]; and mental health disorders [32,36,39,41,46,47,53,60]. Other apps were specific to pregnancy/obstetric care [29,37,44,59], and one was for postoperative care [49].…”
Section: Resultsmentioning
confidence: 99%
“…No relevant studies were identified via handsearching. As a result, seven studies [4][5][6][12][13][14][15] were included (see Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Specific to self-monitoring tools for patients with AF, there are other published studies that demonstrated that patients were generally satisfied with a mobile self-care and medication adherence app [ 12 , 13 ]. In the study by Hirschey et al [ 12 ], the majority of the participants reported using the medication reminder feature, despite stating that they would have remembered to take their medication without the app. Participants also liked that they were able to check their heart rates quickly.…”
Section: Discussionmentioning
confidence: 99%
“…This is in stark contrast to our findings that such features in an e-tool were not seen to be useful and illustrate the importance of understanding the patient population for whom an e-tool is designed. In the study by Hirschey et al [ 12 ], the patients had an average age of 59 years, and the majority had at least some college education. Our participants were older and had much less formal education; more than 63% of Singaporeans aged 65 years or older in 2018 did not attain more than primary school education [ 18 ].…”
Section: Discussionmentioning
confidence: 99%